Fabrication of lithium substituted copper ferrite (Li-CuFe2O4) thin film as an efficient gas sensor at room temperature - Manikandan, V. (H. : ĐHQGHN, 2018)
A Li-CuFe2O4thinfilm has a well-defined nanocrystalline structure with a crystallite size of ~17 nm. The TEM and SEM images of the Li-CuFe2O4thinfilm show a polyhedron shape of nanoparticles with uneven sizes, resulting in a significant change in its gas sensing characteristics such as sensitivity and sensor response. An optical analysis shows that the Li-CuFe2O4thinfilm has a semiconducting nature, and the band gap of the thinfilm is determined to be 1.15 eV. The gas sensor analysis demonstrates repeatability of the sensing behavior of the Li-CuFe2O4 thin film and this ensures a reliable and efficient gas sensor at room temperature.